Respons Of Erythrocytes, Hematocrit And Hemoglobin River Catfish (Mystus Nemurus) Combination Fed Guava Leaves (Psidium Guajava) And Bitter (Andrographis Paniculata Ness) - Mesi Susanti; Iesje Lukystiowati; Henni Syawal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted from April-June 2013 in the Laboratory of Aquaculture and Fish Diseases and Parasites Laboratory Faculty of Fisheries and Marine Sciences University of Riau. The purpose of this study was to determine the response of erythrocytes, hematocrit, and blood hemoglobin river catfish (Mystus nemurus) fed a combination of guava leaves and bitter infected with the bacterium A. hydrophila. This study used 5 treatments of: negative control (without any solution guava, bitter and non-infected A. hydrophila fish meal), Kp: positive control (without guava leaves and a bitter and infected A. hydrophila fish meal), P1 (addition of guava leaves as much 10 g and 10 g bitter / kg of feed fish meal), P2 (addition of guava leaves and bitter as much as 20 g of 20 g / kg of feed fish meal), P3 (addition of guava leaves and bitter as much as 30 g of 30 g / kg of feed fish meal). The results showed that feeding a combination of guava leaves and bitter can not increase erythrocytes, hematocrit, and hemoglobin but it can increase endurance fish seen from passing fish alive after are infected A. hydrophila. Average erythrocytes from 0.52 to 2.90 million cells/mm3, 16.60 to 50.97% hematocrit and hemoglobin percentage from 3.62 to 5.33 g /%Key word: River catfish (Mystus nemurus), guava leaves and bitter, A. hydrophila